Analysis of Prospective Teacher Ability in Developing Educational Websites using Google Sites - Riwanto, Mawan Akhir; Budiarti, Wahyu Nuning; Dwiyanti, Aris Naeni; Mey Prihandani Wulandari; Romadhon, Ibni Mas'ud Wafaur; Eleonor Francisco (Universitas Sarjanawiyata Tamansiswa, 2024)
This study examines the competencies of future primary school teachers and prospective guidance and counseling instructors in creating instructional websites with Google Sites. It examines how these prospective educators employ the platform to provide dynamic and interactive resources that facilitate diverse educational objectives. The current research evaluates the capacity to design a website structure, register a Google account, organize the main page of Google Sites, insert images and videos, manage menus, and construct inter-page linkages. The research sample included twenty participants, consisting of ten students from the Elementary School Teacher Education Department and ten students from the Guidance and Counseling Department at Nahdlatul Ulama Al Ghazali University, Cilacap, Indonesia. The findings reveal that prospective teachers exhibited proficiency in creating structured and functional websites with Google Sites, while also integrating diverse multimedia elements, including images and interactive features, to enrich the learning experience for their future students.